Servant Leadership, Empowerment, And Church Spiritual Growth in Pentecostal Churches Within Nairobi Metropolitan Counties, Kenya – A Mixed Methods Study - Shaasha Isaac (PAC University, 2025)
Globally, the church is in dire need of spiritual growth so as to fulfil Christ’s great commission to all believers in accomplishment of evangelism and discipleship mission. Servant leadership and empowerment of church members is a key element that could be leveraged to trigger church spiritual growth. The general objective of this study was to assess the effect of servant leadership and empowerment on church spiritual growth in Pentecostal Churches in Kenya within the Nairobi metropolitan counties. The specific objectives of the study entailed: to assess the effect of stewardship on church spiritual growth; to evaluate the effect of commitment to growth of church members on church spiritual growth; to evaluate the effect of community building on church spiritual growth; and to establish how empowerment moderates the relationship between servant leadership and church spiritual growth. Qualitatively, the study explored perceptions of participants on the extent to which church members’ empowerment moderated the relationship between servant leadership and church spiritual growth. The study selected Pentecostal Evangelical Fellowship of Africa; Kenya Assemblies of God, and Full Gospel Churches of Kenya, all under the umbrella of National Council of Churches of Kenya. The study was guided by servant leadership, empowerment, and spiritual leadership theories. The research was mainly anchored on the pragmatism philosophy. The study employed an embedded mixed method approach. Descriptive cross-sectional survey research design and exploratory designs were adopted for data collection and analysis. Data collection was undertaken through questionnaires and interview guides. The target population constituted 2000 church pastors, elders as well as members from which a sample of 333 was obtained through purposive and stratified random sampling techniques. Quantitative data was analyzed using descriptive statistics, correlation and regression analysis, where the Statistical Package for the Social Sciences (SPSS) version 29 was used. The results revealed that servant leadership and church spiritual growth had a strong positive relationship with a correlation coefficient of r=0.707; commitment to growth of people with r=0.665 whereas community building and stewardship had r=0.580 and r=0.450 respectively. Empowerment of church members had a strongly significant moderating effect in the relationship between servant leadership and church spiritual growth with a p-value of <0.05. Qualitative data analysis was done using thematic analysis where it was revealed that servant leadership and empowerment were key elements in enhancing church spiritual growth. The study recommended that Pentecostal churches should embrace servant leadership, strengthen face to face evangelism, enhance volunteer services, promote spiritual formation, collaborate with other churches and improve provision of rewards so as to boost church spiritual growth.